2019
DOI: 10.1038/s41598-019-43052-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dapagliflozin Effectiveness as Add-on Therapy for the Treatment of Type 2 Diabetes Mellitus in a Qatari Population

Abstract: The effectiveness of dapagliflozin in the management of type-2 diabetes mellitus (T2-DM) is an essential issue for establishing a basis for prescribing dapagliflozin. This study aimed to assess the effectiveness of dapagliflozin in combination with other hypoglycemic agents (OHAs) in reducing glycated hemoglobin (HbA1c) and fasting blood glucose (FBG) at 3, 6, 9 and 12 months. This retrospective observational study included all patients who visited the endocrine clinics at Hamad Medical Corporation (HMC) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…10 In a study by Moustafa et al Dapagliflozin significantly reduced the HbA1c level and FBG of type 2 diabetes patients as add-on therapy, regardless of the type of the co-administered OHA or insulin. 11 In a study by Strojek et al revealed that although incidents suggestive of genital infections were recorded more frequently in patients on dapagliflozin, it was usually well tolerated and dramatically improved HbA1c in patients with uncontrolled T2DM on sulphonyl urea monotherapy. 12 The results of current study also revealed that Dapagliflozin significantly improved the glycemic control of Type-2 diabetic patients when used in combination with standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a study by Moustafa et al Dapagliflozin significantly reduced the HbA1c level and FBG of type 2 diabetes patients as add-on therapy, regardless of the type of the co-administered OHA or insulin. 11 In a study by Strojek et al revealed that although incidents suggestive of genital infections were recorded more frequently in patients on dapagliflozin, it was usually well tolerated and dramatically improved HbA1c in patients with uncontrolled T2DM on sulphonyl urea monotherapy. 12 The results of current study also revealed that Dapagliflozin significantly improved the glycemic control of Type-2 diabetic patients when used in combination with standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Fadini et al [15] reported similar results from the Italian observational study DARWIN-T2D; in >17,000 patients on dapagliflozin, there was a significant improvement in HbA1c levels (−0.7% [8 mmol/mol]) after an average of 5.5 months of treatment. Additionally, a more recent study assessed the effectiveness of dapagliflozin on T2DM patients and found that the administration of dapagliflozin as add-on therapy in combination with standard diabetic treatments decreased HbA1c levels significantly by 0.8% (9 mmol/mol) after 6 months and by 1.5% (16 mmol/mol) after 12 months [16]. Moreover, a randomized phase III trial conducted on treatment-naive Asian patients with T2DM demonstrated a −1.04% (11 mmol/mol) and 1.11% (12 mmol/mol) mean reduction in their HbA1c level after 24 weeks of treatment with 5 mg and 10 mg dapagliflozin, respectively [17].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Our findings were corroborated by a more recent research which shown that Dapagliflozin, when administered in conjunction with other OHAs or insulin, successfully lowered HbA1c level and FBG within 6-12 months. 32 Multiple analyses of SGLT2 inhibitors have shown dapagliflozin to be effective. Studies [33][34] showed its efficacy as monotherapy for newly diagnosed T2-DM patients.…”
Section: Discussionmentioning
confidence: 99%